Association between Musculoskeletal Status and Genetic Mutations in Patients with Hemophilia A - Primacakti, Fitri; Wahidiyat, Pustika Amalia; Sjarif, Damayanti R.; Chozie, Novie Amelia; Candini, Naura Anindya; Prihartono, Joedo; Sukartini, Ninik; Ramadhani, Nadhifa Tazkia; Lubis, Bidasari (Writing Center IMERI FMUI, 2025)
Introduction: Hemophilia A is an inherited bleeding disorder caused by mutations in the factor VIII (FVIII) gene. These mutations result in either reduced FVIII synthesis (null variants) or loss of FVIII function (non-null variants). Null variants are typically associated with more severe FVIII deficiency and recurrent joint bleeding, which may adversely affect musculoskeletal health. Objective: To evaluate the relationship between musculoskeletal status and genetic mutations in patients with hemophilia A. Methods: A cross-sectional study was conducted at the Faculty of Medicine Universitas Indonesia-Dr. Cipto Mangunkusumo Hospital from June 2024 to March 2025. Genetic analysis was performed at the Human Genetic Research Center using inverse-shifting PCR and Sanger sequencing. Mutations were classified as null variants (intron-22 inversion, intron-1 inversion, large deletion, and nonsense mutations) and non-null variants (missense and non-conserved splice mutation). Musculoskeletal status was assessed by the presence of target joints and the Hemophilia Joint Health Score (HJHS), which evaluates global gait and joint function of the elbows, knees, and ankles. Higher HJHS scores indicate worse joint health. Results: Sixty patients were included in this study, of which 39 had severe, 15 had moderate, and the remaining 6 had mild hemophilia A. The median age was 9.5 years (range 2-18). Null variants were identified in 45/60 patients and non-null variants in 15/60 patients. The most common target joints were the knees in patients with null variants and the ankles in those with non-null variants. The median HJHS was 4 (Q1-Q3: 2-13.5) in the null variant group and 2 (Q1-Q3: 1-11) in the non-null variant group. No significant association was observed between the target joint and the HJHS and genetic mutations. Further subgroup analysis showed no difference in HJHS between mutation groups among patients receiving prophylaxis (p=0.366) or on-demand treatment (p=0.458). Conclusion: No association was found between genetic mutation type and musculoskeletal status in patients with Hemophilia A. HJHS did not differ between mutation groups regardless of treatment regimens.